Towards a Lifelong Active Society: Coping with Japan's Changing Population. Issue 3 (26th September 2016) - Seike, Atsushi
Abstract: In order to cope with Japan's globally unprecedented ageing population, it is extremely important to promote the employment of older people. By taking advantage of the strong motivation among Japanese older people to continue working, Japan will be able to establish a lifelong active society in which the will and ability of older people can be fully utilized. In order to promote a lifelong active society we need to revise our public pension scheme so as not to discourage older workers to continue working. The mandatory retirement practice should also be revised along with the seniority based wage system to promote the employment of older workers. The creation of a lifelong active society should substantially reduce the burden on future generations, and in particular the social security burden. If Japan can establish a lifelong active society, it will have valuable implications for other countries facing population ageing.